Effect of multistrain probiotic supplementation in individuals with type 2 diabetes mellitus - Firouzi, Somayyeh (2015)
Probiotics is reported as one of the option to achieve optimum glycemic control. While findings in animal models were convincing, evidences from human clinical trial are still controversial. To address this research gap, the double blind randomized controlled trial was conducted to investigate the effect of 12 weeks supplementation with multistrain probiotics in individuals with type 2 diabetes. A total of 136 participants with Type 2 Diabetes and aged 30-70 (mean Body Mass index (BMI): 29.2 kg/m2 in Probiotic Group and 29.3 kg/m2 in Placebo Group; Mean Glycated Hemoglobin (HbA1c): 7.6% in Probiotic Group and 7.5% in Placebo Group) participated in the study. Participants were asked to maintain their dietary intake and physical activity levels throughout the study. Participants were randomly assigned to receive daily dose of 6×1010 multistrain probiotic supplement. Changes in glycemic control variables, anthropometric measures, BMI, fasting lipid, renal profile, liver function, blood pressure, and high sensitivity C-reactive protein were measured at baseline, week 6 and 12 of the study. Adherence was assessed by calculating the number of remaining sachets. In a sub-samples (n=40), their stool were collected to determine the Colony Forming Units (CFUs) of Lactobacillus and Bifidobacterium using the plate count method. Sensitivity analyses namely Intention to Treat (ITT) and Per Protocol (PP) analyses were performed using General Linear Model Analysis of Variance. The ITT analysis conducted on the full set of data while the PP analysis was performed on those who have completed the study with more than 85% adherence. Baseline characteristics of the participants were comparable in both groups except for the liver status. The attrition rate was 20.6%. Participants maintained their dietary intake and physical activity throughout the study period. HbA1c decreased 0.2% in Probiotic Group while remains unchanged in Placebo Group. These differences were not significant between Probiotics and Placebo Groups in ITT analyses but in PP analysis, the differences were significant (p=0.017). Fasting insulin increased 0.8 μU/mL in the Placebo Group and decreased 1.6 μU/mL in the Probiotic Group. These changes were significant in both the ITT (p=0.020) and PP (p=0.016) analyses. Serum urea levels reduced by 0.22 mmol/L in the Probiotic Group while it increased by 0.21 mmol/L in Placebo Group and the differences were significant in ITT analysis (p=0.018). Other outcomes did not change significantly between groups. In a subsamples, the Lactobacillus (from 6.4×106 to 1.3×107 CFU/g; p=0.05) and the Bifidobacterium (from 3.4×106 to 1.3×107 CFU/g; p=0.02) species were significantly increased in Probiotics Groups as compared to Placebo Group in ITT Multistrain probiotics supplementation for a 12-week period influenced glycemic control variables and diabetes-related outcomes in individuals with Type 2 Diabetes. It was effective to improve the fasting insulin and urea levels as well. The improvements in HbA1c levels were also greater among those participants who have completed the trial with good adherence.